2010
DOI: 10.1590/s0004-27302010000300006
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between variants of the leptin gene and obesity and metabolic biomarkers in Brazilian individuals

Abstract: Objective:The relationship between variants of the leptin gene (LEP) and obesity and metabolic biomarkers was investigated in Brazilian individuals. Subjects and methods: One-hundred-ten obese (BMI > 30 kg/m 2 ) and 100 non-obese individuals (145 women and 65 men, aged 49 ± 14 years) were randomly selected. Plasma leptin, glycemia, serum lipid measurements and LEP -2548G>A and 3'HVR polymorphisms were analyzed. Results: The LEP -2548GG genotype was associated with a 2.2% and 2.0% increase in BMI (p = 0.009) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 37 publications
3
20
0
6
Order By: Relevance
“…The allele frequency of the G2548A polymorphism observed in our study is in accordance with that of other studies (Le Stunff et al, 2000;Mammès et al, 2000;Walley et al, 2006;Hinuy et al, 2008Hinuy et al, , 2010Huuskonen et al, 2010) except for one population from Taiwan, where the G allele frequency was lower than the A allele (Wang et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…The allele frequency of the G2548A polymorphism observed in our study is in accordance with that of other studies (Le Stunff et al, 2000;Mammès et al, 2000;Walley et al, 2006;Hinuy et al, 2008Hinuy et al, , 2010Huuskonen et al, 2010) except for one population from Taiwan, where the G allele frequency was lower than the A allele (Wang et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…The detailed characteristics of these studies are shown in table 1. In 9 articles published between 2006 and 2012, 1,372 obese subjects and 1,616 controls were involved from a wide range of regions including Europe [19,21,22,27], South America [18,23,25] and North Africa [24,26]. Of the selected studies, 6 related to a Caucasian population and 3 to a South American population (mixed race).…”
Section: Resultsmentioning
confidence: 99%
“…There were 2 studies in which the genotypes in the control group were not in HWE [26,27]. Two studies were performed by the same investigator [23,25], and it is not clear whether different individuals were genotyped or whether some individuals were counted twice (the author rejected our inquiry e-mail). Both studies were included in the final analysis, and the influence of a possible partial overlap on the overall OR was assessed by subgroup analysis after excluding the older one [23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Obese (n = 100) and non-obese (110) Information on age, hypertension, hyperglycemia, coronary artery disease (CAD) investigated by coronary angiography, smoking and sedentary lifestyle were recorded, and data were described elsewhere (19). Measurements of BMI, waist circumference (WC), waist-to-hip ratio (WHR) were taken.…”
Section: Study Populationmentioning
confidence: 99%